Digital media strategies to riase awareness of the risks climate changes in Iraq - Jassim Tarish Al-Aqabi, Asst. Prof. Dr (lark, 2024)
The study sought to monitor and analyze digital media strategies in the nature of media treatment of environmental issues and climate change in Iraq, based on the directives and warnings of the United Nations, which described in its report issued in 2023 that climate change portends a terrifying and miserable future in which desertification, hunger, and homelessness are widespread, and Volker Türk criticized The United Nations Commissioner for Human Rights told world leaders, “Because they do not realize the magnitude of the coming danger and look at the climate crisis in the short term, the future of hunger and suffering should be bequeathed to our children, and we do not have to do that. We are the generation that possesses the most powerful technological tools in history that enable us to change and adapt to The new transformations that began to strike the world more than thirty years ago.))To achieve the objectives of the study, the researcher relied on the method of content analysis within the framework of the survey studies approach, where the websites of the institutions concerned with climate affairs in Iraq were analyzed, namely (the Ministry of Environment, the Ministry of Water Resources, the Ministry of Agriculture, the Ministry of Science and Technology, and the Meteorology Authority) for a period of 1 / 3/2023 until 12/31/2023, which is the period during which the United Nations called on countries around the world to take media, awareness and technological action to address the climate crisis. The theory of social responsibility was employed in the study because it is one of the closest scientific theories that integrates media, community protection, and state responsibilities.The study also included the use of a survey tool for the opinion of academic elites in Iraqi universities for a sample of (184) male and female teaching staff on evaluating the digital media performance of the institutions in the study sample to solve awareness of the dangers of climate change.The study found that there was media interest from the institutions concerned with the study, but it did not rise to the level of the expected risks indicated by the United Nations. The media treatments included a number of various digital communication strategies on websites, where the education strategy ranked first out of the total of ten strategies that were classified in the framework. Theoretically, the results showed that websites rely primarily on news reports within the framework of the media arts used. While the majority of the sample of academics believes that media performance was average in its attention compared to the size of the problem.
Keywords: strategies, digital media, awareness, climate risks